Vertical niche definition of test‐bearing protists (Rhizaria) into the twilight zone revealed by in situ imaging. (15th June 2020) - Biard, Tristan; Ohman, Mark D.
Abstract: The Rhizaria is a super‐group of amoeboid protists with ubiquitous distributions, from the euphotic zone to the twilight zone and beyond. While rhizarians have been recently described as important contributors to both biogenic silica and carbon fluxes, we lack the most basic information about their ecological habitats and preferences. Here, using in situ imaging (Underwater Vision Profiler 5), we characterize the vertical ecological niches of different test‐bearing pelagic rhizarian taxa in the southern California Current Ecosystem . We define three vertical layers between 0 and 500 m occupied, respectively, by (1) surface dwelling and mostly symbiont‐bearing rhizarians (Acantharia and Collodaria), (2) flux‐feeding phaeodarians in the lower epipelagic (100–200 m), and (3) Foraminifera and Phaeodaria populations adjacent to the oxygen minimum zone. We then use Generalized Additive Models to analyze the response of each rhizarian category to a suite of environmental variables. The models explain between 9% and 93% of the total variance observed for the different groups. While temperature and the depth of the deep chlorophyll maximum appear as the main abiotic factors influencing populations in the upper 200 m, dissolved silicon concentration is related to the abundance of mesopelagic phaeodarians, though it explains only a portion of the variance. The importance of biotic interactions (e.g., prey availability, predation, parasitism, symbiosis) is still to be considered, in order to fully incorporate the dynamics of test‐bearing pelagic rhizarians in ecological and biogeochemical models.